Analysis of Syntactic Errors in English Writing by Advanced Students in the Faculty of Economics and Business - Hariaty, Rismala Sri; Ramdani, Akhmad Subkhi; Zulkifli, Irwan; Mardiyah, Mutmainatul (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
English is crucial for university students because it provides access to a wide range of academic resources and global knowledge. This study aims to analyze the types and frequency of syntactic errors in English writing by advanced students at the Faculty of Economics and Business. The research method used was a combination of qualitative and quantitative descriptive methods, with an error analysis approach. Data were obtained from academic essays written by 30 final-year students. The analysis showed that the most frequent syntactic errors were errors in the use of complex sentence structures, subject-verb imbalances, tense errors, and inappropriate use of conjunctions. The main factors causing these errors were a lack of in-depth understanding of English grammar rules and the influence of the structure of their first language (Indonesian). Furthermore, most students lacked formal experience in academic writing training, so they tended to translate directly from Indonesian and use tools such as Google Translate. Although some students made improvements, such as rereading their writing or using grammar-checking applications, these efforts were not consistently implemented. These findings are expected to provide evaluation material for academic English teaching, particularly in strengthening grammar aspects at the university level. This study also recommends error analysis-based learning strategies to improve students' writing skills.